2018
DOI: 10.1016/j.scitotenv.2018.05.215
|View full text |Cite
|
Sign up to set email alerts
|

A model-based projection of historical state of a coastal ecosystem: Relevance of phytoplankton stoichiometry

Abstract: We employed a coupled physical-biogeochemical modelling framework for the reconstruction of the historic (H), pre-industrial state of a coastal system, the German Bight (southeastern North Sea), and we investigated its differences with the recent, control (C) state of the system. According to our findings: i) average winter concentrations of dissolved inorganic nitrogen and phosphorus (DIN and DIP) concentrations at the surface are ∼70-90% and ∼50-70% lower in the H state than in the C state within the nearsho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 81 publications
(74 reference statements)
1
29
0
Order By: Relevance
“…This suggests that light or P limitation surpass N limitation even under TN and winter DIN concentrations being about 25 % lower in that region in the WFD scenario. This is in agreement with Kerimoglu et al (2018), who used a high-resolution model of the southern North Sea and also found light limitation to play a major role in this region. Other studies also identified P as the main limiting nutrient in the inner German Bight (Lenhart et al, 2010;Emeis et al, 2015;Wakelin et al, 2015), which suggests that additional P reductions might be required to achieve the "good environmental status" in the German Bight.…”
Section: Changes In Nitrogen and Chlorophyll-a In The North Sea In Resupporting
confidence: 92%
See 3 more Smart Citations
“…This suggests that light or P limitation surpass N limitation even under TN and winter DIN concentrations being about 25 % lower in that region in the WFD scenario. This is in agreement with Kerimoglu et al (2018), who used a high-resolution model of the southern North Sea and also found light limitation to play a major role in this region. Other studies also identified P as the main limiting nutrient in the inner German Bight (Lenhart et al, 2010;Emeis et al, 2015;Wakelin et al, 2015), which suggests that additional P reductions might be required to achieve the "good environmental status" in the German Bight.…”
Section: Changes In Nitrogen and Chlorophyll-a In The North Sea In Resupporting
confidence: 92%
“…In order to calculate the individual reductions in DIN and PON, we calculate the average DIN:PON ratios for the individual German rivers during the period 2006-2012, as agreed on with stakeholders from the German Federal Environmental Agency, using the above described daily river dataset. With that, we translate the TN target concentration into target concentrations for DIN and PON and calculate the reduction levels based on their 2006-2012 average concentrations, following Kerimoglu et al (2018). As DIN:PON ratios vary between the different German rivers and throughout the seasonal cycle, we obtain different reductions levels for these rivers as well as for DIN and PON.…”
Section: Model Setup and Nitrogen Reduction Scenariomentioning
confidence: 99%
See 2 more Smart Citations
“…As in Kerimoglu et al (2017b), assimilated and un-assimilated fractions of the ingested prey by each zooplankton j are determined by the assimilation efficiency X j (B23),B24), which is continuously adjusted (as in Grover, 2002), such that the zooplankton can maintain their homeostatic elemental composition. Here this scheme was extended to multiple nutrients, i.e., N and P, and X are calculated iteratively, similar to that in (Kerimoglu et al, 2018). Starting from each X set to default values 470 (Table B5), if P to be ingested would be less than the amount required to match the ingested C, C is down-regulated, and vice versa:…”
Section: B1 Planktonic Componentsmentioning
confidence: 99%